PROTOCOLO DE COMUNICAÇÃO PÚBLICA SOBRE A SOCIOEDUCAÇÃO NO INSTAGRAM: case para a Fundação da Criança e do Adolescente - SILVA, Priscilla Swaze Anchieta (2022)
This research proposes to formulate a protocol of Public Communication on the subject of Socioeducation for Instagram, with application to the Fundação da Criança e do Adolescente. To achieve the proposed objectives, this research adopts a qualitative approach, using research techniques: Systematized Bibliographic, Documentary, Interviews, Focus Group mixed with the Restorative Circles methodology. To analyze the collected data, the second method to be used was Content Analysis, focusing on the Public Communication, Socio-education and Social Media categories. The elements pointed out in the research subsidize the basis for the construction of the protocol "Socioeducation in the digital Environment and construction of new narratives".